Concomitant use of radiofrequency and high intensity focused electromagnetic field energies for full‐body remodeling: MRI evidence‐based prefatory trial. (31st August 2022) - Katz, Bruce
Abstract: Background: Radiofrequency and HIFEM have been used as standalone modalities in body contouring. The novel device allows their synchronous emission simultaneously in a single applicator. Objectives: This prelusive trial aims to investigate the safety and efficacy of such treatment when used on multiple body parts on the same day for a full‐body remodeling. Methods: Three female subjects (21.0 ± 2.0 years) underwent 4 treatment sessions. The treatment was applied to the abdomen, saddlebags, inner thighs, and buttocks, during each visit, lasting 30 min for each site. The outcomes were assessed through examination of MRI images acquired at baseline and 3 months post‐treatment. Fat and muscle thickness were measured at predefined locations. Weight and waist, hip, and thigh circumference records along with digital photographs were also taken. Results: Fat thickness measurement showed a reduction of 17.57 ± 3.22 mm in the saddlebag region, 12.43 ± 1.93 mm in inner thighs, and 10.65 ± 1.26 mm in the abdomen. The fat in the buttock region showed negligible changes. The muscle thickness increased on average by 2.98 ± 0.60 mm for rectus abdominis and 7.42 ± 1.56 mm for gluteus maximus. The circumferential reduction was also observed on the waist (7.83 ± 2.25 cm), at the level of outer thighs (2.83 ± 1.53 cm), and inner thighs (3.58 ± 1.84 cm). Digital photographs showed noticeable improvement in the overall body appearance. The treatments were safe, and no side effects were noted. Conclusion: The preliminary outcomes indicate that the procedure delivering HIFEM and RF simultaneously on multiple body areas on the same day could be an effective and comfortable treatment for fat reduction on multiple body parts, thickening of underlying muscles, and overall improved aesthetic appearance.